Ambientalidades: jornalismo ambiental e educomunicação em podcast - Paula, João Pedro Ferreira de [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
This final course assignment report describes the production of Impacto Ambiental podcast series' first episode. Impacto Ambiental is an environmental journalism project established at Faculty of Architecture, Arts and Communication of UNESP Bauru. Based on the knowledge and debates on educommunication and environmental journalism, Ambientalidades was conceived as an information source which encourages discussions on the issues it approaches. The podcast aims to relate with the reality of Brazilian teenagers in senior year of high school. Ambientalidades' episodes connect relevant social discussions and their impacts on the environment with Brazilian schools coursework

Relatório do Projeto Experimental de Conclusão do Curso de Jornalismo, que objetivou produzir o primeiro episódio de uma série de podcasts do projeto Impacto Ambiental, da FAAC-Unesp Bauru. A partir dos entendimentos e discussões sobre a educomunicação e o jornalismo ambiental, o Ambientalidades foi pensado como uma fonte de informação e debate agradável, conectada com a realidade do jovem brasileiro pré-vestibulando do ensino médio. As pautas do Ambientalidades são feitas ligando os assuntos em discussão na sociedade e seus impactos no meio ambiente com as disciplinas escolares
Keywords: Educomunicação; Jornalismo eletrônico; Internet; Educomunication